DHA Supplementation during Pregnancy in Women with Obesity Normalizes IGF2R Levels in the Placenta of Male Newborns - Juan José Castro; Adriana Umana-Perez; Erika Castaño-Moreno; Paola Casanello; Ana María Ronco (International Journal of Endocrinology)
Introduction. Insulin-like growth factor receptor 2 (IGF2R) regulates placental nutrient transport, and its soluble form is related to obesity in adults. If the placental expression of IGF2R is altered in women with obesity is unknown. Whether maternal supplementation with docosahexaenoic acid (DHA), a polyunsaturated fatty acid with anti-inflammatory properties, has a modulatory role in IGF2R’s function has not been elucidated. We hypothesized that maternal obesity (Ob) would be associated with alterations in placental IGF2R expression, which may be prevented with DHA supplementation during pregnancy. Methods. At delivery, we obtained placentas from women with Ob (BMI ≥ 30 kg/m2, n = 17), Ob supplemented with 800 mg/day of DHA during pregnancy (Ob + DHA, n = 13), and normal-weight women (Nw, BMI ≥ 18.5 ≤ 24.9 kg/m2, n = 14). The IGF2R mRNA and protein were determined by RT-PCR and western blotting, respectively. Moreover, we quantified the gene expression of molecules that modulate the IGF2R function in the extracellular domain, such as TACE/ADAM17, PLAU, and IGF2. Mann–Whitney and Kruskal–Wallis nonparametric tests were used to compare results between two or three groups accordingly. Results. The IGF2R levels in the Ob placentas of the male offspring were higher than in the Nw group. The DHA supplementation prevented this effect, suggesting an unknown relationship between IGF2R-Ob-DHA in placental tissues. Conclusion. We report, for the first time, that DHA supplementation during pregnancy in women with obesity normalizes the increased IGF2R levels in male placentas, reducing the risk of adverse outcomes related to the IGF2/IGF2R system in male newborns.